(untitled) - Evans, Patrick (Hoboken, N.J., 2007)
Evans writes with urgency, in nearly breathless prose punctuated by bulleted lists and a direct first-person voice to the reader. His advice is sensible, detailed, and backed up by examples.
Keywords: Selling